BIOCHEMICAL CHANGES OF CERTAIN PLANT SPECIES DUE TO VARIOUS DRYING TREATMENTS - Pandith Javid Iqbal (Indonesian Journal of Pharmacy, 2012)
Phytochemical analysis of the Indian medicinal plants to identify the therapeutically active chemical compounds in them and  clinically  testing  for  their  efficacy  and  risks  is  an inescapable  procedure,  to  provide  new  sources  of  natural products  to  the  pharmaceutical  industry.  Therefore,  the phytochemical  screening  studies  should  be  concentrated  on the  hitherto  unexplored  medicinal  plants  for  their  medicinal values.  In  the  current  study  the  leaves  of  different  medicinal plants  like  Achyranthus  aspera,  Acalypha  indica,  Euphorbia hirta,  Lindenbergia  indica,  Parthenium  hysterophorus  and Pesistrophe  bicalyculata  were  taken  for  the  chlorophyll  and carotenoid  estimation  by  the  method  of  Jayaraman  (1981). The  leaves  of  the  following  plants  were  allowed  to  dry  in  an oven at different temperatures, time period and freeze drying. Oven  drying  was  done  at  50±10C  for  9  hours  and  at  70±1ºC for  5  hours.  Results  obtained  revealed  that  both  the  drying treatments  affect/decrease  the  chlorophyll  content  of  all  the six  plants.  The  maximum  effect  was  seen  in  Euphorbia  hirta (93.97%)  for  oven  drying  at  50±1ºC  for  9  hours.  The minimum  effect  was  observed  in  Parthenium  hysterophorus (21.68%)  for  oven  drying  at  70±1ºC  for  5  hours  and Achyranthus  aspera  (11.56%)  for  freeze  drying.  The  leaf preparations  treated  by  oven  drying  was  found  to  have  lower chlorophyll  and  carotenoid  content  as  compared  to  freeze drying  which  in  turn  has  lower  chlorophyll  content  as compared to fresh extracts.Key words:   Chlorophyll  content,  Drying  treatments,  and  leaf extract.